PELAKSANAAN PEMBIAYAAN PEMILIKAN RUMAH (PPR) DENGAN MENGGUNAKAN AKAD MUSYARAKAH MUTANAQISHAH PADA BANK KALBAR SYARIAH CABANG SAMBAS - laras laras (Sebi : Studi Ekonomi dan Bisnis Islam, 2023)
The presence of Home Ownership Financing (HOF) is due to the demand of the community in meeting housing needs in installments. The product is managed by a conventional bank. However, over time people want a home financing product that is in accordance with sharia principles. Home Ownership Financing (HOF) products used in shari'a banking have various differences from Home Ownership Credit (HOC) in conventional banking. The purpose of this research is to find out the implementation and constraints of Home Ownership Financing (HOF) using the Musyarakah Mutanaqishah contract at Bank Kalbar Syariah Sambas Branch. This research uses a type of descriptive qualitative research, which only explains situations and events derived from interviews, observations, and documentation on the implementation of Home Ownership Financing (HOF) using the Musyarakah Mutanaqishah agreement at Bank Kalbar Syariah Sambas Branch conducted by researchers coming directly to Bank Kalbar Syariah Sambas Branch. The results of this study the implementation of Home Ownership Financing (HOF) at the Sambas branch of Bank Kalbar Syariah are in accordance with sharia principles, especially the contract used, namely the musyarakah mutanaqishah contract which is in accordance with DSN-MUI fatwa No. 73 / DSN / MUI / XI / 2008 which states that musyarakah financing has advantages in togetherness and justice, both in sharing profits and risks of loss, so that it can be an alternative in the process of ownership of assets (goods) or capital, ownership of assets (goods) or capital can be done by using the musyarakah mutanaqishah contract, that in order for this method to be carried out in accordance with sharia principles, DSN-MUI considers it necessary to establish a fatwa on musyarakah mutanaqishah to serve as a guideline.